2006
DOI: 10.1177/1086026606294957
|View full text |Cite
|
Sign up to set email alerts
|

Building the Future by Looking to the Past

Abstract: Organizations and environment (O&E) researchers focus on either organizational outcomes or environmental outcomes. In this article, the authors argue that these are significantly different approaches to O&E research. The first aims to contribute to organization theory and performance; the latter aims to improve environmental performance. With a starting position that most research published in influential general management journals is of the organizational outcomes variety, the authors reviewed O&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(33 citation statements)
references
References 110 publications
1
32
0
Order By: Relevance
“…These topics have evolved and become related to others, thus enabling progress in the discipline from the beginning, when it focused on the introduction of a green or environmental dimension and its effects on results, up to the present day in which the management of quality, in particular, the development of ISO regulations and topics related to corporate social responsibility, has acquired a great deal of importance. In addition, we have identified that the "observations" proposed by Bansal and Gao (2006) remain current and some of them have been developed. In that sense, environmental management research has a growing role in the main Management and Business journals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These topics have evolved and become related to others, thus enabling progress in the discipline from the beginning, when it focused on the introduction of a green or environmental dimension and its effects on results, up to the present day in which the management of quality, in particular, the development of ISO regulations and topics related to corporate social responsibility, has acquired a great deal of importance. In addition, we have identified that the "observations" proposed by Bansal and Gao (2006) remain current and some of them have been developed. In that sense, environmental management research has a growing role in the main Management and Business journals.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the term PERFORMANCE, authors such as Porter and Van der Linde (1995) and Hart and Ahuja (1996) highlight one of the research questions that has attracted the most attention in the area: "Does it pay to be green?" According to Bansal and Gao (2006), one of the specific features of this field of study is that many works analyse the influence of environmental management on economic performance, environmental performance or both.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To review the articles related to strategic philanthropy, the literature search by Montinel and Delgado-Ceballos (2014) was used. Their literature search on corporate sustainability was based on the work of Bansal and Gao (2006) who located articles in the organisations and environment area by searching for keywords among the top academic journals in the field of general management. Bansal and Gao's list of journals was expanded by Montiel (2008) by adding organisational behaviour journals, strategy journals and journals devoted to the social issues of management and sustainability.…”
Section: Data Collectionmentioning
confidence: 99%